2018
DOI: 10.3389/fmicb.2018.00452
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Four Distinct Phylogenetic Groups in Flavobacterium columnare With Fish Host Associations

Abstract: Columnaris disease, caused by the Gram-negative bacterium Flavobacterium columnare, is one of the most prevalent fish diseases worldwide. An exceptionally high level of genetic diversity among isolates of F. columnare has long been recognized, whereby six established genomovars have been described to date. However, little has been done to quantify or characterize this diversity further in a systematic fashion. The objective of this research was to perform phylogenetic analyses of 16S rRNA and housekeeping gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 51 publications
7
82
0
1
Order By: Relevance
“…Among the genomovar I isolates, only 0901393 is highly virulent, while CDI‐A causes little to no disease (Declercq et al, ). More recent work has also sought to reclassify F. columnare isolates through genotypic analyses into four distinct categories (Lafrentz et al, ). We have thus far relied on the classically defined genomovar system (Kayansamruaj et al, ); however, we would be remiss if we did not point out that it is possible that our current classification of these isolates could differ under the new genetic grouping system.…”
Section: Discussionmentioning
confidence: 99%
“…Among the genomovar I isolates, only 0901393 is highly virulent, while CDI‐A causes little to no disease (Declercq et al, ). More recent work has also sought to reclassify F. columnare isolates through genotypic analyses into four distinct categories (Lafrentz et al, ). We have thus far relied on the classically defined genomovar system (Kayansamruaj et al, ); however, we would be remiss if we did not point out that it is possible that our current classification of these isolates could differ under the new genetic grouping system.…”
Section: Discussionmentioning
confidence: 99%
“…Columnaris disease, caused by the Gram‐negative bacterium Flavobacterium columnare , is one of the leading causes of disease losses to many aquaculture industries worldwide. It has been suggested that the development of effective prevention and control measures may have been hampered by a lack of a complete understanding of the genetic diversity (LaFrentz et al, ). The genetic diversity of F. columnare was first realized over 30 years ago (Song, Fryer, & Rohovec, ), and since that time, different molecular techniques have been used to investigate diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, LaFrentz et al () performed a multilocus phylogenetic analysis of 50 F. columnare isolates and used the genotype determined by 16S‐RFLP (i.e. genomovar) as the basis for comparison of the derived phylogenies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations